Differences Between the Psychological Symptoms of Health Workers and General Community After the First Wave of the COVID-19 Outbreak in Spain - Reno-Chanca, Sergio; Van Hoey, Julie; Santolaya-Prego de Oliver, Jesús Alberto; Blasko-Ochoa, Ilargi; Sanfeliu Aguilar, Pilar; Moret-Tatay, Carmen (Frontiers in Psychology, 2021)
Covid-19 has worsened the physical and mental health of the general population. Healthcare workers have a high risk of suffering a mental disorder after the first wave. In this way, Psychologists, who deal with mental health issues and are considered as healthcare workers in many countries, are of interest in this context. The aim of this study is to examine anxiety, depression, stress, and obsessions and compulsions across psychologists, health care professionals, and the general community. These variables were measured through the Depression, Anxiety, and Stress Scale (DASS-21), as well as the Yale–Brown Obsessive Compulsive Scale (Y-BOCS), which were related to different sociodemographic variables. The study was carried out after the first wave in Spain through an online questionnaire. Structural equation modelling and a multigroup analysis were carried out across groups and variables under study. The results suggested that; i) Health care workers and general community depicted similar results in anxiety and stress, as well as obsessions; ii) The group of psychologist described better scores than other groups under study; iii) Stress and anxiety did not predict compulsions in the group of psychologist; iv) Anxiety predicted obsessions for all professions, while the relationship of this variable with stress was different for each group; v) Invariance reached a full metric level.